Mangosteen Agribusiness Partnership In PT. Radja Manggis Sejati, Padangan Village, Tabanan Regency - Luh Putu Kirana Pratiwi; Nyoman Yudiarini; Ida Ayu Made Dwi Susanti (Warmadewa University Press, 2022)
One of the agricultural sub-sectors that apply the mangosteen commodity partnership pattern in Bali is STA Sari Buah with PT Radja Manggis Sejati in Padangan Village, Pupuan District, Tabanan Regency. The development of partnerships can help farmers and business actors in increasing the growth of horticultural agribusiness, especially in the mangosteen commodity. The marketing partnership pattern for the mangosteen commodity is based on a written agreement, but the marketing contract is made between suppliers and farmer groups with exporter companies. Responsibilities of partner groups, namely: taking an inventory of group members and mangosteen trees, cultivating mangosteen properly, collecting mangosteen from farmers, sorting and grading with partner company officers, selling mangosteen to partner companies, and repaying capital loans by deducting from the proceeds of mangosteen sales. . The rights of partner group members are to obtain loans, to be able to supply mangosteen to partner companies, to obtain prices according to the prevailing market prices, to receive payments by bank transfer as soon as the goods are received by the partner companies, and to receive a fee for each kilogram of mangosteen deposited.